2015
DOI: 10.1017/s1463423615000535
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to statistics in primary health care physicians, Qassim province

Abstract: PHC physicians have a positive attitude to statistics. However, they realize their gaps in knowledge in statistics, and are keen to fill these gaps. Statistics training, resulting in improved statistics knowledge is expected to lead to clinical care utilizing evidence-based medicine, and thus improvement to health care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…Previous studies have shown that medical students have a misconception about the difficulty of learning biostatistics concepts and have reported cases such as concern and anxiety, negative attitudes, lack of motivation, lack of interest, and not understanding the practical importance or value of statistics in students (22)(23)(24)(25)(26)(27)(28). The present study showed that MSc nursing students experienced more effective learning in the intervention group compared to the control group.…”
Section: Discussionsupporting
confidence: 42%
“…Previous studies have shown that medical students have a misconception about the difficulty of learning biostatistics concepts and have reported cases such as concern and anxiety, negative attitudes, lack of motivation, lack of interest, and not understanding the practical importance or value of statistics in students (22)(23)(24)(25)(26)(27)(28). The present study showed that MSc nursing students experienced more effective learning in the intervention group compared to the control group.…”
Section: Discussionsupporting
confidence: 42%
“…The research variables were the attitude towards statistics, statistics achievement, academic achievement, and field of study. The attitude was defined psychologically (Ashaari et al, 2011;Chiesi & Primi, 2009;Gal, Ginsburg, & Schau, 1997;Hannula et al, 2016;Hilton et al, 2004;Jahan et al, 2016). Based on their definitions, operational variable of attitudes toward statistics (ATS) can be written as a tendency of students' respond on statistics topic.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 15 articles showed there was statistically relation between attitudes toward statistics and statistics achievement, but two other articles showed the different things. Jahan, Al-Saigul, & Suliman (2016) examined the association between attitudes toward statistics and statistical ability and they expressed that someone who has positive attitudes toward statistics still indicated a difference in terms of statistical ability or achievement. Based on the major of studies, Ashaari et al (2011) stated that there was no significant difference in attitudes toward statistics.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of publications should not be used as a surrogate marker for increasing quality of education, as was once suggested [4]. Perhaps the reduced number of publications suggests the need for more research-oriented training programmes [5]; nonetheless, monitoring of productivity should be centralised and reported annually by the Saudi Commission for Health Specialties. Monitoring should include the study design, the sample size and the productivity based on the programme, institution and province.…”
Section: Discussionmentioning
confidence: 99%